AKSES JENIS DOKUMEN PADA BASIS DATA TERPADU: SUATU TINJAUAN TERHADAP OPAC DI PDII-LIPI - Ade Kohar (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2001)
Integrated data base is a data base records bibliographic data of several types of document like textbook, periodicals, proceedings, research report, thesis, and article. Purposes of this study were to investigate document type description and searching strategy in integrated data base of online public access catalogs (OPAC) in PDII-LIPI, and to know user opinion about that data base existence. It used observation and interviews to 100 data base users to collect data. Result of this study stated that document type description in OPAC was not indexed, so users couldn't do information searching of special type of document directly in the data base. There was only one method could be used to search information of special type of document. User could select it from some information records on the computer screen as the result of document title, author name or subject searching in the data base. This information access method was not efficient. So document type description and indexing was an important factor and should be done in information retrieval system using integrated data base. But respondent majority (84%) in PDII-LIPI stated that they liked using separated data base to search information of special type of document.